Association between handgrip strength and body composition, physical fitness, and biomarkers in postmenopausal women with metabolic syndrome - Miranda,Humberto (2022)
SUMMARY OBJECTIVES: This study examined the association between handgrip strength and body composition, physical fitness, and biomarkers in postmenopausal women with metabolic syndrome. METHODS: A total of 75 postmenopausal women were diagnosed with metabolic syndrome participated in this study. Muscle strength was assessed via a hydraulic grip strength dynamometer; physical fitness tests included a timed-up-and-go, arm curl test, and 30-s chair stand. Body composition was assessed via bioelectrical impedance, from which estimates of fat mass, body fat percentage, fat-free mass, and visceral fat area were determined. Fasting plasma glucose and glycated hemoglobin were measured via blood sample analyses. Multiple linear regression analyses were conducted using handgrip strength as the dependent variable and using body composition, physical fitness, and biomarkers as independent variables. RESULTS: The results revealed that 52% of the total sample were classified as obese, 37.3% as overweight, and only 10.7% as normal weight. Significant correlations were present between handgrip strength and fat-free mass (p=0.002; R=0.590), mean blood pressure (p=0.002; R=0.450), and arm curl (p=0.001; R=0.795). CONCLUSION: This study showed that handgrip strength was predictive of fat-free mass, blood pressure, and upper limb strength performance.